2020
DOI: 10.1186/s12870-020-02340-4
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of nutrition activity of a microgranule fertilizer fortified with proteins

Abstract: Background: A microgranule fertilizer was designed for localized fertilization of soil with controlled release of nutrients. The microgranule matrix was fortified with proteins, which were obtained from food industry byproducts or waste, i.e., whey protein from milk serum, soy protein from soy isolate and egg white protein from chicken egg white powder. The mechanism of the protein decomposition and migration of micro and macromolecule compounds through two different model soil systems was investigated. The po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Based on this fact, the results indicated that whey protein hydrolysates (after 8 h) had a considerable potential antioxidant activity where pepsin hydrolyzed protein showed the highest one. Similar results were obtained when using microgranules enriched with protein [38,39].…”
Section: Discussionsupporting
confidence: 84%
“…Based on this fact, the results indicated that whey protein hydrolysates (after 8 h) had a considerable potential antioxidant activity where pepsin hydrolyzed protein showed the highest one. Similar results were obtained when using microgranules enriched with protein [38,39].…”
Section: Discussionsupporting
confidence: 84%
“…PH are produced from both plant and animal protein sources using partial hydrolysis [9], which consists of a mixture of peptides, oligopeptides, and amino acids. However, they may have carbohydrates, small quantities of mineral elements, phenols, and other compounds [10] that have shown promising influence on plant growth performances [11]. PH are used in broad areas, including medicine, nutrition, food, and agriculture, due to their nutritional and functional/bioactive properties [12].…”
Section: Introductionmentioning
confidence: 99%
“…The resulting fertiliser had the following content: 136.81 P(g kg −1 ), 3.2 N (g kg −1 ), 29.96 K (g kg −1 ), 13.20 Mg (g kg −1 ), 347.81 Ca (g kg −1 ), 3.93 Na (g kg −1 ), 1 Fe (g kg −1 ), 0.8 Zn (mg kg −1 ), 3.2 Cu (mg kg −1 ), and 6.5 Mn (mg kg −1 ) [18]. Microgranule for precision application is distinguished by a well-proven mechanism enabling controlled release of ammonia nitrogen and amino acids during hydrolysis of protein additive [20].…”
Section: Characteristics Of the Applied Fertilisersmentioning
confidence: 99%
“…This resulted from the use of microgranules for precision application into the soil at the time of maize seed planting. This fertiliser contains protein which, owing to the unique mineral base of the amendment, is dissolved in the soil environment; as a result, ammonia nitrogen and amino acids are released [20]. These components directly affect the nutritional status of plants in the initial stages of growth, which is reflected by the values of NDVI.…”
Section: Normalised Difference Vegetation Index (Ndvi)mentioning
confidence: 99%